Influence of the Transformational Style of Leadership on Job Satisfaction in Healthcare Units in Poland - Wojciech Głód (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The presented paper addresses the relationship between the transformational style of leadership and job satisfaction. The theoretical part of the study discusses different variables and mutual relations between them. The empirical part contains the results of research carried out in 4 selected healthcare units among 525 employees. The conducted research indicates that it is necessary to strengthen the employee's position in order to increase their job satisfaction. In this way, initiation becomes a factor not only positively affecting job satisfaction, but also mediating in the relationship between the transformational leadership and job satisfaction. The presented findings suggest that this political intervention must include both transformational leadership and empowerment in order to increase job satisfaction among both medical and administrative staff.
Keywords: 650; Transformational leadership; job satisfaction; healthcare; Poland